Study on dynamic response and loading mitigation characteristics of liquid-filled cell under drop-weight impact. (1st December 2021) - Zhao, Zhujie; Li, Dian; Hou, Hailiang; Yao, Menglei; Wuang, Ke
Graphical abstract: Highlights: There are two deformation stages and four deformation/failure modes of cell structures subjected to impact. Water pressure changes the deformation of the cell walls from instability-bending to instability-bulging. The extrusion force of water in the liquid-filled cell reduces the possibility of the overall instability of the structure. The cell structure with concave configuration has a better cushioning effect than that with cubic configuration. Abstract: In order to explore the anti-impact properties of the liquid-filled structure, concave and cuboid cell structures are selected for drop weight impact tests and finite element numerical analysis with and without liquid filled in the structures. Dynamic deformations were observed using high-velocity photography, and dynamic strains at typical positions were tested. The final failure modes of the cells were obtained using the 3D scanner. Then the deformation/failure processes and modes of the structures, the variation of the energy absorption ratio of each wall and the mitigation characteristics of the cell to the impact load were analyzed, and the influence of impact velocity of the drop hammer and cell wall thickness were discussed. The results showed that water medium reduced the risk of the overall instability of the cell structure; the water pressure changed the cell wall deformation from instability-bending to instability-bulging; the cell structure with concave configuration has better cushioning effect than that with cuboid configuration.